Meningkatkan Positif WOM Melalui Kualitas Pelayanan dan Nilai Pelanggan: Peran Kepuasan Pelanggan sebagai Variabel Mediasi - Dosma Sherina Ramawaty; Bonifasius MH Nainggolan (LPPM Universitas Asa Indonesia, 2023)
This research was made to examine the impact of customer value and service quality on the creation of positive WOM through customer satisfaction at Kopi Kenangan. This research was conducted using primary data that had been collected through survey questionnaires. Using purposive sampling as a sampling treatment technique, as well as with the help of SEM-PLS in examining the hypotheses that have been set. The analysis in this study was carried out through two stages, where the first stage was testing the validity and reliability, and the next stages respectively were the estimation and validation of the path coefficient and the stability of the structural model. Each hypothesis of variables was tested, using the Smart-PLS V.3.2.9 software, with 226 customers of Kopi Kenangan ruko Arundina Cibubur as respondents. In this study it was found that customer value influences customer satisfaction and positive WOM, service quality influences customer satisfaction but is proven not to affect positive WOM, and customer satisfaction is proven to mediate. This research was made to examine the impact of customer value and service quality on the creation of positive WOM through customer satisfaction at Kopi Kenangan. This research was conducted using primary data that had been collected through survey questionnaires. Using purposive sampling as a sampling treatment technique, as well as with the help of SEM-PLS in examining the hypotheses that have been set. The analysis in this study was carried out through two stages, where the first stage was testing the validity and reliability, and the next stages respectively were the estimation and validation of the path coefficient and the stability of the structural model. Each hypothesis of variables was tested, using the Smart-PLS V.3.2.9 software, with 226 customers of Kopi Kenangan ruko Arundina Cibubur as respondents. In this study it was found that customer value influences customer satisfaction and positive WOM, service quality influences customer satisfaction but is proven not to affect positive WOM, and customer satisfaction is proven to mediate.